Individual and combined effects of ice sheets and precession on MIS-13 climate - Q. Z. Yin; A. Berger; M. Crucifix (Copernicus Publications, 2009)
An Earth System Model of Intermediate Complexity is used to investigate the role of insolation and of the size of ice sheets on the regional and global climate of marine isotope stage (MIS) 13. The astronomical forcing is selected at two dates with opposite precession, one when northern hemisphere (NH) summer occurs at perihelion (at 506 ka (1 ka=1000 years) BP), and the other when it occurs at aphelion (at 495 ka BP). Five different volumes of the Eurasian ice sheet (EA) and North American ice sheet (NA), ranging from 0 to the Last Glacial Maximum (LGM) one, are used. The global cooling due to the ice sheets is mainly related to their area, little to their height. The regional cooling and warming anomalies caused by the ice sheets intensify with increasing size. Precipitation over different monsoon regions responds differently to the size of the ice sheets. Over North Africa and India, precipitation decreases with increasing ice sheet size due to the southward shift of the Intertropical Convergence Zone (ITCZ), whatever the astronomical configuration is. However, the situation is more complicated over East Asia. The ice sheets play a role through both reducing the land/ocean thermal contrast and generating a wave train which is topographically induced by the EA ice sheet. This wave train contributes to amplify the Asian land/ocean pressure gradient in summer and finally reinforces the precipitation. The presence of this wave train depends on the combined effect of the ice sheet size and insolation. When NH summer occurs at perihelion, the EA is able to induce this wave train whatever its size is, and this wave train plays a more important role than the reduction of the land/ocean thermal contrast. Therefore, the ice sheets reinforce the summer precipitation over East China whatever their sizes are. However, when NH summer occurs at aphelion, there is a threshold in the ice volume beyond which the wave train is not induced anymore. Therefore, below this threshold, the wave train effect is dominant and the ice ...